Antimicrobial susceptibility and ribotypes of Clostridium difficile isolates from a Phase 2 clinical trial of ridinilazole (SMT19969) and vancomycin. (30th April 2018) - Snydman, David R; McDermott, Laura A; Thorpe, Cheleste M; Chang, Justin; Wick, Jenna; Walk, Seth T; Vickers, Richard J
Abstract: Objectives: We evaluated the antimicrobial susceptibility and ribotypes of Clostridium difficile isolates from participants in a Phase 2 study of ridinilazole, a novel targeted-spectrum agent for treatment of C. difficile infection. Methods: Participants received ridinilazole (200 mg twice daily) or vancomycin (125 mg four times daily) for 10 days (ClinicalTrials.gov: NCT02092935). The MICs of ridinilazole and comparators for C. difficile isolates from stool samples were determined by agar dilution. Toxin gene profiling was performed by multiplex PCR and ribotype identification by capillary electrophoresis. Results: Eighty-nine isolates were recovered from 88/100 participants (one participant had two strains at baseline). The median colony count (cfu/g stool) was 1.9 × 10 4 (range: 2.5 × 10 2 –7.0 × 10 6 ). Twelve participants (three received ridinilazole and nine received vancomycin) experienced recurrence, confirmed by immunoassays for free toxin in stool samples. The ribotype of eight out of nine isolates obtained at recurrence matched those of the initial isolates. All isolates, including those obtained at recurrence, were susceptible to ridinilazole within the expected range [median (range) MIC: 0.12 (0.06–0.5) mg/L]. The median (range) vancomycin MIC was 1 (0.5–4.0) mg/L. At baseline, 13.6% and 13.3% of samples in the ridinilazole and vancomycin groups were positive for VRE, increasing to 23.7% and 29.7% by day 40, respectively. Common ribotypes included 014-20 (14 isolates), 027 (13), 106 (7), 002 (7), 078-126 (4), 001 (4), 087 (3) and 198 (3). Toxin gene profiling of nearly all baseline isolates (98.9%) revealed a binary toxin gene ( cdtA/cdtB) prevalence of 35%. Conclusions: Ridinilazole potently inhibited recovered C. difficile isolates. Recurrence was not associated with altered susceptibility.